Increased urinary nitrite, a marker of nitric oxide, in active inflammatory bowel disease - Michael G. Goggins; Syed A. Shah; Jason Goh; Anil Cherukuri; Donal G. Weir; Dermot Kelleher; Nasir Mahmud (Mediators of Inflammation)
Background: Nitric oxide (NO) production is increased in inflammatory bowel disease (IBD), and measurement of NO metabolites may be useful for monitoring disease activity.